Social Struggle in Atiq Rahimi’s the Patience Stone An Article - Fanani, Abu; Zaidun, Achmad; Amiq (LP3MKIL, 2022)
This article analyzes social struggle done by the woman against society within her family as well as outside her family. Using social theory of conflict and theme and plot, the study finds that the theme of the story deals with the woman’s social struggle, whilst, in the plot analysis, from the exposition to the resolution, the woman is in social struggle.